Multi-Hit action of membrane active peptides: towards understanding bacterial cell killing - Moiset, Gemma; Cirac, Anna D.; Mika, Jacek T.; Kocer, Armagan; Stuart, Marc C. A.; Sengupta, Durba; Marrink, Siewert-Jan; Poolman, Bert (Biophysical Journal, 2012)
56th Annual Meeting of the Biophysical-Society, San Diego, CA, FEB 25-29, 2012

Molecular Insights into the dynamics of pharmacogenetically important N-terminal variants of the human beta(2)-adrenergic receptor - Shahane, Ganesh; Parsania, Chirag; Sengupta, Durba; Joshi, Manali (Plos Computational Biology, 2014)
The human beta(2)-adrenergic receptor (beta(2)AR), a member of the G-protein coupled receptor (GPCR) family, is expressed in bronchial smooth muscle cells. Upon activation by agonists, beta(2)AR causes bronchodilation and relief in asthma patients. The N-terminal polymorphism of beta(2)AR at the 16th position, Arg16Gly, has warranted a lot of attention since it is linked to variations in response to albuterol (agonist) treatment. Although the beta(2)AR is one of the well-studied GPCRs, the N-terminus which harbors this mutation, is absent in all available experimental structures. The goal of this work was to study the molecular level differences between the N-terminal variants using structural modeling and atomistic molecular dynamics simulations. Our simulations reveal that the N-terminal region of the Arg variant shows greater dynamics than the Gly variant, leading to differential placement. Further, the position and dynamics of the N-terminal region, further, affects the ligand binding-site accessibility. Interestingly, long-range effects are also seen at the ligand binding site, which is marginally larger in the Gly as compared to the Arg variant resulting in the preferential docking of albuterol to the Gly variant. This study thus reveals key differences between the variants providing a molecular framework towards understanding the variable drug response in asthma patients.

Molecular dynamics simulations of GPCR-cholesterol interaction: an emerging paradigm - Sengupta, Durba; Chattopadhyay, Amitabha (Biochimica Et Biophysica Acta-Biomembranes, 2015)
G protein-coupled receptors (GPCRs) are the largest class of molecules involved in signal transduction across cell membranes and represent major targets in the development of novel drug candidates. Membrane cholesterol plays an important role in GPCR structure and function. Molecular dynamics simulations have been successful in exploring the effect of cholesterol on the receptor and a general consensus molecular view is emerging. We review here recent molecular dynamics studies at multiple resolutions highlighting the main features of cholesterol-GPCR interaction. Several cholesterol interaction sites have been identified on the receptor that are reminiscent of nonannular sites. These cholesterol hot-spots are highly dynamic and have a microsecond time scale of exchange with the bulk lipids. A few consensus sites (such as the CRAC site) have been identified that correspond to higher cholesterol interaction. Interestingly, high plasticity is observed in the modes of cholesterol interaction and several sites have been suggested to have high cholesterol occupancy. We therefore believe that these cholesterol hot-spots are indicative of `high occupancy sites' rather than `binding sites'. The results suggest that the energy landscape of cholesterol association with GPCRs corresponds to a series of shallow minima interconnected by low barriers. These specific interactions, along with general membrane effects, have been observed to modulate GPCR organization. Membrane cholesterol effects on receptor structure and organization, that in turn influences receptor cross-talk and drug efficacy, represent a new frontier in GPCR research. This article is part of a Special Issue entitled: Lipid-protein interactions. Guest Editors: Amitabha Chattopadhyay and jean-Marie Ruysschaert. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Coarse-grain simulation; CRAC; GPCR; Lipid-receptor interaction; Membrane cholesterol; Receptor dimerization

Molecular mechanism underlying recruitment and insertion of lipid-anchored LC3 protein into membranes - Thukral, Lipi; Sengupta, Durba; Ramkumar, Amrita; Murthy, Divya; Agrawal, Nikhil; Gokhale, Rajesh S. (Biophysical Journal, 2015)
Lipid modification of cytoplasmic proteins initiates membrane engagement that triggers diverse cellular processes. Despite the abundance of lipidated proteins in the human proteome, the key determinants underlying membrane recognition and insertion are poorly understood. Here, we define the course of spontaneous membrane insertion of LC3 protein modified with phosphatidylethanolamine using multiple coarse-grain simulations. The partitioning of the lipid anchor chains proceeds through a concerted process, with its two acyl chains inserting one after the other. Concurrently, a conformational rearrangement involving the alpha-helix III of LC3, especially in the three basic residues Lys(65), Arg(68), and Arg(69), ensures stable insertion of the phosphatidylethanolamine anchor into membranes. Mutational studies validate the crucial role of these residues, and further live-cell imaging analysis shows a substantial reduction in the formation of autophagic vesicles for the mutant proteins. Our study captures the process of water-favored LC3 protein recruitment to the membrane and thus opens, to our knowledge, new avenues to explore the cellular dynamics underlying vesicular trafficking.

Membrane-induced organization and dynamics of the N-terminal domain of chemokine receptor CXCR1: insights from atomistic simulations - Kharche, Shalmali; Joshi, Manali; Sengupta, Durba; Chattopadhyay, Amitabha (Chemistry and Physics of Lipids, 2018)
The CXC chemokine receptor 1 (CXCR1) is an important member of the G protein-coupled receptor (GPCR) family in which the extracellular N-terminal domain has been implicated in ligand binding and selectivity. The structure of this domain has not yet been elucidated due to its inherent dynamics, but experimental evidence points toward membrane-dependent organization and dynamics. To gain molecular insight into the interaction of the N-terminal domain with the membrane bilayer, we performed a series of microsecond time scale atomistic simulations of the N-terminal domain of CXCR1 in the presence and absence of POPC bilayers. Our results show that the peptide displays a high propensity to adopt a beta-sheet conformation in the presence of the membrane bilayer. The interaction of the peptide with the membrane bilayer was found to be transient in our simulations. Interestingly, a scrambled peptide, containing the same residues in a randomly varying sequence, did not exhibit membrane-modulated structural dynamics. These results suggest that sequence-dependent electrostatics, modulated by the membrane, could play an important role in folding of the N-terminal domain. We believe that our results reinforce the emerging paradigm that cellular membranes could be important modulators of function of G protein-coupled receptors such as CXCR1.
Keywords: All atom MD simulations; beta-sheet; CXCR1; Membrane interaction; N-terminal

Molecular determinants of GPCR oligomerization - Mohole, Madhura; Kumar, G. Aditya; Sengupta, Durba; Chattopadhyay, Amitabha (Molecular determinants of GPCR oligomerization, 2020)

Molecular interplay at the membrane and impact on cellular physiology - Pucadyil, Thomas; Kulkarni, Kiran; Sengupta, Durba (Journal of Membrane Biology, 2021)

Molecular determinants of GPCR pharmacogenetics: deconstructing the population variants in β2-adrenergic receptor - Joshi, Manali; Nikte, Siddhanta; Sengupta, Durba (Advances in Protein Chemistry and Structural Biology, 2022)
G protein-coupled receptors (GPCRs) are membrane proteins that play a central role in cell signaling and constitute one of the largest classes of drug targets. The molecular mechanisms underlying GPCR function have been characterized by several experimental and computational methods and provide an understanding of their role in physiology and disease. Population variants arising from nsSNPs affect the native function of GPCRs and have been implicated in differential drug response. In this chapter, we provide an overview on GPCR structure and activation, with a special focus on the β2-adrenergic receptor (β2-AR). First, we discuss the current understanding of the structural and dynamic features of the wildtype receptor. Subsequently, the population variants identified in this receptor from clinical and large-scale genomic studies are described. We show how computational approaches such as bioinformatics tools and molecular dynamics simulations can be used to characterize the variant receptors in comparison to the wildtype receptor. In particular, we discuss three examples of clinically important variants and discuss how the structure and function of these variants differ from the wildtype receptor at a molecular level. Overall, the chapter provides an overview of structure and function of GPCR variants and is a step towards the study of inter-individual differences and personalized medicine.

Molecular mechanisms underlying caveolin-1 mediated membrane curvature - Prakash, Shikha; Malshikare, Hrushikesh; Sengupta, Durba (Journal of Membrane Biology, 2022)
Caveolin-1 is one of the main protein components of caveolae that acts as a mechanosensor at the cell membrane. The interactions of caveolin-1 with membranes have been shown to lead to complex effects such as curvature and the clustering of specific lipids. Here, we review the emerging concepts on the molecular interactions of caveolin-1, with a focus on insights from coarse-grain molecular dynamics simulations. Consensus structural models of caveolin-1 report a helix-turn-helix core motif with flanking domains of higher disorder that could be membrane composition dependent. Caveolin-1 appears to be mainly surface-bound and does not embed very deep in the membrane to which it is bound. The most interesting aspect of caveolin-1 membrane binding is the interplay of cholesterol clustering and membrane curvature. Although cholesterol has been reported to cluster in the vicinity of caveolin-1 by several approaches, simulations show that the clustering is maximal in membrane leaflet opposing the surface-bound caveolin-1. The intrinsic negative curvature of cholesterol appears to stabilize the negative curvature in the opposing leaflet. In fact, the simulations show that blocking cholesterol clustering (through artificial position restraints) blocks membrane curvature, and vice versa. Concomitant with cholesterol clustering is sphingomyelin clustering, again in the opposing leaflet, but in a concentration-dependent manner. The differential stress due to caveolin-1 binding and the inherent asymmetry of the membrane leaflets could be the determinant for membrane curvature and needs to be further probed. The review is an important step to reconcile the molecular level details emerging from simulations with the mesoscopic details provided by state of the art experimental approaches. [GRAPHICS] .
Keywords: Cholesterol clustering; Membrane curvature; Protein-lipid interactions

Molecular mechanisms underlying nanowire formation in pristine phthalocyanine - Pinjari, Aadil; Saraf, Deepashri; Sengupta, Durba (Physical Chemistry Chemical Physics, 2023)
Understanding the molecular processes of nanowire self-assembly is crucial for designing and controlling nanoscale structures that could lead to breakthroughs in functional materials. In this work, we focus on pristine phthalocyanines as a representative example of mesogenic supramolecular assemblies and have analyzed the formation of nanowires using classical molecular dynamics simulations. In the simulations, the molecules spontaneously form multi-columnar structures resembling supramolecular polymers that subsequently grow into more ordered aggregates. These self-assemblies are concentration dependent, leading to the formation of multi-columnar, dynamic aggregates at higher concentrations and nanowires at lower concentrations. The multi-columnar assemblies on a whole are more disordered than the nanowires, but have locally ordered domains of parallel facing molecules that can fluctuate while maintaining their overall shape. The nanowire formation at lower concentrations involves the initial interaction and clustering of randomly oriented phthalocyanine molecules, followed by the merging of small clusters into elongated segments and the eventual formation of a stable nanowire. We observe three main conformers in these self-assemblies, the parallel, T-shaped and edge-to-edge stacking of the phthalocyanine dimers. We calculate the underlying free energy landscape and show that the parallel conformers form the most stable configuration which is followed by the T-shaped and edge-to-edge dimer configurations. The findings provide insights into the mechanisms and pathways of nanowire formation and a step towards the understanding of self-assembly processes in supramolecular mesogens. Understanding the molecular processes of nanowire self-assembly of phthalocyanine molecules.

Membrane remodeling by the caveolin-1 8s oligomeric complex - Malshikare, Hrushikesh; Sengupta, Durba (Biophysical Journal, 2025)
Caveolin-1 is a scaffolding protein crucial for the formation of caveolae, specialized membrane structures that are involved in diverse cellular processes such as endocytosis, mechanosensing, and lipid regulation. Recently, a unique structure of the 8S oligomeric complex of caveolin-1 was resolved by cryoelectron microscopy, providing a foundational basis for understanding its molecular mechanisms. In this study, we probe the membrane interactions of the oligomeric caveolin-1 complex in membrane lipid bilayers and vesicles. We performed coarse-grained molecular dynamics simulations to delineate the interactions of the palmitoylated and nonpalmitoylated caveolin-1 with multicomponent membranes. During the simulations, the caveolin-1 complex binds to the membranes, partially to one of the leaflets in a shallow monotopic arrangement. A remodeling of the lipids in its vicinity of the complex was observed in both vesicles and planar bilayers. However, the caveolin-1 complex binds to vesicles without inducing any significant change to the curvature, whereas it appears to induce increased curvature in the planar bilayers leading to the formation of highly curved nanodomains. Cholesterol and phosphoserine lipid enrichment, hallmarks of caveolin-1 binding, were observed in a membrane topology-dependent manner. The differential cholesterol clustering observed between vesicles and bilayers highlights the curvature-dependent nature of caveolin-1-mediated lipid organization. Our work highlights the dual significance of lipid organization and membrane topology in the functional dynamics of caveolin-1, shedding light on its role in inducing and sensing membrane curvature, which is pivotal for various cellular processes. SIGNIFICANCE The rather unanticipated experimental structure of the oligomeric complex of caveolin-1 has opened up multiple questions such as how caveolin-1 interacts with cell membranes and how curvature can be induced or stabilized by a relatively flat protein complex. Here, we identify the molecular mechanisms underlying membrane curvature by caveolin-1 using coarse-grained molecular dynamics simulations. We show that the caveolin-1 complex can bind in a shallow monotopic arrangement and initiate clustering cholesterol and phosphoserine lipids. In vesicles, caveolin-1 binding does not lead to differences in curvature, but binding to planar bilayer leads to the formation of highly curved nanodomains. Our work is an important step to identify novel mechanisms of caveolin-1 stabilized or induced membrane curvature.

Molecular interactions of the pioneer transcription factor GATA3 With DNA - Gharui, Sowmomita; Sengupta, Durba (Proteins-Structure Function and Bioinformatics, 2025)
The GATA3 transcription factor is a pioneer transcription factor that is critical in the development, proliferation, and maintenance of several immune cell types. Identifying the detailed conformational dynamics and interactions of this transcription factor, as well as its clinically important population variants will allow us to unravel its mode of action. In this study, we analyze the molecular interactions of the GATA3 transcription factor bound to dsDNA as well as three clinically important population variants by atomistic molecular dynamics simulations. We identify the effect of the variants on the DNA conformational dynamics and delineate the differences compared to the wildtype transcription factor that could be related to impaired function. We highlight the structural plasticity in the binding of the GATA3 transcription factor and identify important DNA-protein contacts. Although the DNA-protein contacts are persistent and appear to be stable, they exhibit nanosecond timescale fluctuations and several binding/unbinding events. Further, we identify differential DNA binding in the three variants and show that the N-terminal binding is reduced in two of the variants. Our results indicate that reduced minor groove width and DNA diameter are important hallmarks for the binding of GATA3. Our work is an important step towards understanding the functional dynamics of the GATA3 protein and its clinically significant population variants.
Keywords: DNA-protein interactions; GATA protein; Molecular dynamics simulations; molecular mechanism; population variants; transcription factor

A Molecular View of Lipid Nanoparticles: Insights into their Morphology and Structural Plasticity - Porte, Sudha; Vadhana, V.; Sengupta, Durba (Small, 2025)
Lipid nanoparticles (LNPs) have emerged as versatile delivery vehicles for nucleic acid-based therapeutics. Despite their increasing importance, the molecular structure and physico-chemical characteristics of LNPs still remain unclear. In this review, the structural features and phase behavior of LNPs are highlighted. First, the various compositional elements, such as cationic lipids, helper lipids and sterols are discussed, illustrating their functional roles in the self-assembly and stability of LNPs. Molecular models derived from experimental and computational approaches are discussed to provide insights into the structural organization of the LNP components. The influence of sterols and helper lipids in modulating LNP architectures, including membrane fluidity and phase separation, which are key factors for both fusion potential and endosomal escape, is discussed. Variations in sterol content and headgroup chemistry can induce transitions from lamellar to non-lamellar structures, thereby influencing gene transfection outcomes. Further, how cationic lipids induce structural phase transitions, such as lamellar-to-hexagonal and inverse cubic rearrangements under physiological and acidic pH, mimicking extracellular and endosomal conditions, are described. These transitions play a pivotal role in ribonucleic acid (RNA) release and membrane fusion events. This comprehensive review allows to reconcile molecular and structural dynamics that would be necessary for rational design of RNA delivery systems.
Keywords: drug delivery; lipid nanoparticles; phase separation; vaccine delivery

Mechanistic principles of antimicrobial peptides uncovered by charge density-based machine learning - Malshikare, Hrushikesh; Priyakumar, U. Deva; Chatterjee, Prathit; Sengupta, Durba (Chemical Communications, 2026)
Antimicrobial peptides (AMPs) are emerging as potent alternatives to conventional antibiotics, yet their diverse nature due to divergent mechanisms of action hinders rational design. Here, we present an electrostatics-stratified computational framework that uncovers key physicochemical principles governing AMP activity. Experimentally validated peptides were grouped by average charge per residue (i.e., the charge/length of the peptide) and analyzed through integrated sequence-, structure-, and chemistry-based descriptors. Distinct molecular signatures emerged across electrostatic regimes: low-charge/length peptides rely on amphipathic organization via structural compactness, whereas the intermediate-charge/length peptides exhibit balanced hydrophobicity and electrostatics. The high-charge peptides couple strong cationic attraction with lipophilicity and tryptophan anchoring to mainly disrupt membranes. Interestingly, hydrophobic moment, which is a measure of the amphipathicity, is found to be important in all three classes of AMPs. This study identifies distinguishing features of AMP sub-groups and suggests design guidelines for developing selective and potent next-generation AMPs.